Interplay Between Ion Channels and the Wnt/β-Catenin Signaling Pathway in Cancers - Rapetti-Mauss, Raphael; Berenguier, Camille; Allegrini, Benoit; Soriani, Olivier (Frontiers in Pharmacology, 2020)
Increasing evidence point out the important roles of ion channels in the physiopathology of cancers, so that these proteins are now considered as potential new therapeutic targets and biomarkers in this disease. Indeed, ion channels have been largely described to participate in many hallmarks of cancers such as migration, invasion, proliferation, angiogenesis, and resistance to apoptosis. However, at the molecular level, the development of cancers is characterised by alterations in transduction pathways that control cell behaviours. Indeed, the interactions between ion channels and cancer-related signalling pathways is poorly understood so far. Nevertheless, a limited number of reports have recently addressed this important issue, especially regarding the interaction between ion channels and one of the main driving forces for cancer development: the Wnt/β-catenin signalling pathway. In this review, we propose to explore and discuss the current knowledge regarding the interplay between ion channels and the Wnt/β-catenin signalling pathway in cancers.